Evaluation of bladder function in children with familial mediterranean fever and outcomes: A retrospective study - Sevim YENER; Şeyma TÜRKMEN; Mehmet Oğuzhan AĞAÇLI; Zekeriya İLÇE; Betül SÖZERİ (BMC Urology)
Abstract Background The aim of this study was to investigate bladder functions in patients diagnosed with familial Mediterranean fever but without urological complaints using non-invasive methods. Materials and methods Patients aged between 6 and 17 years diagnosed with FMF were included in the study. Complete urinalysis, ultrasonography (renal parenchymal thickness, hydronephrosis, bladder wall thickness, postmicturition residual urine) were recorded for the patients. Uroflowmetry was performed for the patients. Results A total of 51 patients were included in the study, 28 of whom were female (54.9%) and 23 were male (45.1%). The mean age of the patients was 11.8 (± 3.8) years. Hydronephrosis was detected in 3 patients (5.9%) in the ultrasonography. The mean bladder wall thickness measured was 1.14 (± 1.6) mm. Significant postmicturition residual urine (> 20 ml) was recorded in 15 patients. There was a statistically significant positive relationship between uroflowmetry bladder capacity (UFM-BV) values (p < 0.001). Normal Q max values were measured in 9 patients (17.6%). Conclusion Considering the inflammatory effect of FMF, it is important to evaluate bladder function in asymptomatic patients with parameters measured by uroflowmetry to predict its long-term effects. Additionally, ultrasonographic measurement may be misleading in the evaluation of bladder capacity.